1998
DOI: 10.1093/ajcp/110.4.443
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Oncoprotein Positivity and High MIB-1 (Ki-67) Proliferative Rate Are Independent Predictive Markers for Recurrence in Prostate Carcinoma

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
49
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 15 publications
10
49
0
Order By: Relevance
“…Similar results have also been reported for esophageal, cervical and head, and neck carcinomas and colorectal adenocarcinomas (36,37,38). In Hodgkin's lymphoma, association of prostate carcinomas, testicular carcinomas, and acute myelogenous leukemia has been described to have opposite effects, with higher expression values being associated with a dismal prognosis (39,40,41,42). The antiapoptotic role of BCL2 has been well characterized but the exact mechanism by which BCL2 might exert its protective effect on some kinds of cancers is still unclear.…”
Section: Discussionsupporting
confidence: 73%
“…Similar results have also been reported for esophageal, cervical and head, and neck carcinomas and colorectal adenocarcinomas (36,37,38). In Hodgkin's lymphoma, association of prostate carcinomas, testicular carcinomas, and acute myelogenous leukemia has been described to have opposite effects, with higher expression values being associated with a dismal prognosis (39,40,41,42). The antiapoptotic role of BCL2 has been well characterized but the exact mechanism by which BCL2 might exert its protective effect on some kinds of cancers is still unclear.…”
Section: Discussionsupporting
confidence: 73%
“…Accordingly in those studies Increased Bcl-2 expression is associated to favorable outcome. While its high expression is associated with poor survival in B-cell chronic lymphocytic leukemia (CLL), prostate cancer and urinary tract transitional cell cancer (Faderal et al, 2002;Keshgegian et al, 1998;Stackhouse et al, 1999). Rostamizadeh et al demonstrated the higher expression levels of the Bcl-2 gene in tumor samples compared with marginal samples, however, this was not a significant difference (p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Which of the dual functions' predominates seem to be tissue specific; for example, increased Bcl-2 expression is associated with unfavorable outcome in B-cell chronic lymphocytic leukemia (CLL) and prostate cancer (Ofner et al, 1995;) whereas its expression is related to increased survival in colorectal and breast carcinoma (Keshgegian et al, 1998;Faderl et al, 2002). apoptosis markers, in particular Bcl-2 and Bax expression, are receiving much attention for their relationship with the cellular response to genotoxic damage in experimental tumors (Chipuk et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…19,[26][27][28][29][30][31][32][33][34][35][36] Overexpression of the BCL-2 gene may predispose dysplastic epithelium to genetic instability, which may lead to neoplasia and the invasive phenotype. To our knowledge, there are no published reports on the relationship between genetic alterations in the antiapoptotic-related gene, namely BCL-2, and prostate cancer risk.…”
Section: Discussionmentioning
confidence: 99%